Migración, diversidad y el aula escolar - Vásquez Salazar, Érika (Revista Electrónica Educare, 2007)
Migrations seems to be an historical constant that have influenced what we are today. Costa Rica receives thousands of inmigrants every year, especially from the neighboring country, Nicaragua. Their presence has transformed our economic and social reality, but mainly it has had a great influence in the dynamic of educational institutions. Therefore, school teachers must be prepared to attend a diverse population, making an effort to offer an education of quality that takes into consideration characteristics of all the actors involved in the process. In order to achieve this, it will be necessary to consider social, economic and emotional aspects, as well as to work for the addition of different elements in the curriculum that allow migrant students to be inserted by providing them a meaningful learning process. Respect for diversity must be achieved by means of an effort to supply a deeper view of the other and its differences, transforming the classroom in an inclusive space for all students.